Pengaruh Digital Marketing, Promo Shopee Tanggal Istimewa dan FOMO terhadap Minat Beli di Marketplace Shopee : Shopee Studi pada Mahasiswa UIN Datokarama Palu - Nanda Lestari; Amanda Amanda; Febriani Febriani; Juriati Bin Sail; Alfian Alfian (MENAWAN : Jurnal Riset dan Publikasi Ilmu Ekonomi, 2025)
The development of digital technology has brought about significant changes in marketing strategies, particularly in the increasingly competitive e-commerce sector. Shopee, as one of the largest marketplaces in Southeast Asia, utilizes digital marketing strategies intensively, including the use of various social media channels, paid advertising, and creative campaigns. Furthermore, Shopee holds massive promotions on special dates such as 9.9, 11.11, and 12.12, packaged with discounts, free shipping, and limited-time offers. This strategy also triggers the Fear of Missing Out (FOMO) phenomenon, where consumers are encouraged to make purchases immediately for fear of missing out on the opportunity to get the best deals. This study aims to analyze the influence of digital marketing, Shopee promotions on special dates, and FOMO on the purchasing interest of students at UIN Datokarama Palu. The study used a quantitative approach with a survey method. The sample consisted of 100 respondents selected using a simple random sampling technique. The research instrument was a questionnaire with a Likert scale, while data analysis was carried out using multiple linear regression using the SPSS program. The results showed that the digital marketing variable (X1) did not have a significant effect on student purchasing interest. In contrast, Shopee's special date promo (X2) and FOMO (X3) proved to have a positive and significant impact. These findings indicate that direct promotional strategies that provide tangible benefits and an emotional, urgency-based approach are more effective in influencing consumer behavior than general digital marketing strategies. Therefore, for e-commerce players, strengthening promotional campaigns that capitalize on specific moments and emotional triggers can be key to increasing sales among young consumers.